2022-VA-1152-ESGO Sigmoid neovagina and double V-Y flap reconstruction after a total pelvic infralevator exenteration. (20th October 2022) - Boria, Felix; Chacón, Enrique; Gutierrez, Monica; Manzour, Nabil; Castellanos, Teresa; Vazquez, Daniel; Chiva, Luis
Abstract : Introduction/Background: Pelvic reconstruction after pelvic exenteration is a challenge for gynecologic oncology surgeons. In this vulvar relapse case, a huge defect was left in the perineum after the exenteration. We decided to do a double V-YT flap in order to fill all the defect and a sigmoid neovagina for the sexual reconstruction and to avoid an empty pelvis syndrome. Methodology: Video edited. Results: . Conclusion: .